Rooting Behaviour Studies in Populus alba Provenances for Different Agro-Forestry Needs - Ramesh, K. R.; Khurana, D. K. (Indian Forester, 2006)
The rooting behaviour of Populus alba provenances in terms of their root characteristics and root pattern were studied. Among the different provenances of P. alba, the variation was observed in their root characteristics in terms of the number of secondary roots, number of tertiary roots and their variation with respect to length of roots, root diameter, fresh root weight and dry root weight at 150 days and 210 days after planting. It was found that, amongst the different provenances the maximum root characteristics were found in Raksham (H.P.), Tirith, Sumoor, Panamic and Tegger (Ladakh). These provenances were found to be effective and superior as compared to other in their root characteristics. The simple correlation studies of root characteristics revealed that number of secondary roots, number of tertiary roots, length of roots, diameter of roots, fresh root weight and dry root weight were positively correlated with each other. The root pattern studies revealed that root pattern remained consistent within a single provenance with less variation. Category ’C’ rooting pattern was found in Bandipura, Sopore, Akpa, Raksham, Tabo, Shampuk and Alchi. So these can be utilized for block planting purposes where water level is high. However, provenances Skupiyan, Manali, Jungi, Morang etc. can be utilized under condition where there is loose soil and the moisture level is less and can perform well under (cold) desert conditions since category ’D’ rooting pattern.